2015
DOI: 10.1007/s13277-015-4445-4
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNAs and tumorigenesis: genetic associations, molecular mechanisms, and therapeutic strategies

Abstract: The human genome contains a large number of nonprotein-coding sequences. Recently, new discoveries in the functions of nonprotein-coding sequences have demonstrated that the "Dark Genome" significantly contributes to human diseases, especially with regard to cancer. Of particular interest in this review are long noncoding RNAs (lncRNAs), which comprise a class of nonprotein-coding transcripts that are longer than 200 nucleotides. Accumulating evidence indicates that a large number of lncRNAs exhibit genetic as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
75
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(75 citation statements)
references
References 157 publications
0
75
0
Order By: Relevance
“…24 Third, lncRNAs regulate protein functions by acting as scaffolds, guiding molecule (in cis or in trans), or decoys. 25,26 Of the limited number of lncRNAs examined so far, MALAT1 is well demonstrated to stimulate tumor progression. 7,27 Robust upregulation of MALAT1 is detected in a variety of cancers (including HCC) or cancers with higher metastatic potential.…”
Section: Discussionmentioning
confidence: 99%
“…24 Third, lncRNAs regulate protein functions by acting as scaffolds, guiding molecule (in cis or in trans), or decoys. 25,26 Of the limited number of lncRNAs examined so far, MALAT1 is well demonstrated to stimulate tumor progression. 7,27 Robust upregulation of MALAT1 is detected in a variety of cancers (including HCC) or cancers with higher metastatic potential.…”
Section: Discussionmentioning
confidence: 99%
“…Yet over 80% of our genome is actively transcribed to a set of RNA transcripts without protein-coding functions [6,7]. Long noncoding RNAs (lncRNAs) are broadly defined as RNAs over 200 nucleotides (nt) in length, which have many structural features of the mRNAs [8][9][10][11]. Accumulating evidence has demonstrated that lncRNAs play important molecular roles in regulating gene expression at the level of transcription and post-transcriptional, and chromatin modification [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…With the development of functional genomics in the past several years, lncRNAs was found to be involved in the gene expression network at various levels, including chromatin modification, transcription, and posttranscriptional processing [9,11,23,24]. Recent reports have shown that aberrant expressions of lncRNAs might alter basic cellular biological processes and contribute to tumorigenesis [25].…”
Section: Discussionmentioning
confidence: 99%